Congenital heart disease associated with the most prevalent chromosomal syndromes: a literature review - Castillo Lam, José Eduardo (2021)
Most frequent chromosomal syndromes like Down, Patau, Edwards, Turner, and Williams affect the pediatric population in various ways, and congenital heart disease explains the altered quality of life they suffer. There is a lack of studies reviewing the cardiac anomalies in these syndromes, and the ones that exist are publications from past decades. We reviewed databases such as MEDLINE, LILACS, SCIELO, and Google Scholar, selecting the best possible evidence, and each chromosomal syndrome was investigated in relation to congenital heart disease, constituting five search groups. The article shows the characteristics of each heart disease described in the studies reviewed, the author, date of publication, country, and population studied, as well as a brief description of the frequency of the disease and its mortality. The results described in this review were contrasted with previous existing literature to verify if there was correspondence between the reported frequencies. The most frequent congenital heart diseases were atrioventricular septal defect (AVSD), ventricular septal defect (VSD), atrial septal defect (ASD), and persistent ductus arteriosus (PDA) in Down syndrome patients, PDA, ASD, and VSD in Patau syndrome patients, AVSD, PDA and valvular defects in Edwards syndrome, bicuspid aortic valve, aortic coarctation and aortic stenosis in Turner syndrome, and supravalvular aortic stenosis and pulmonary stenosis in Williams syndrome.